Clinical profile of stress hyperglycemia in medical intensive care units - Geethanjali Ganesan; Sudha Vidyasagar; Nandakrishna Bolanthakodi; Cynthia Amrutha Sukumar (Clinical Epidemiology and Global Health)
Introduction: Stress hyperglycemia (SH) is a transient increase in blood glucose during acute physiological stress in the absence of glucose homeostasis dysfunction. In the setting of medical intensive care units (ICU), it significantly contributes to patient morbidity and mortality.It initates a cascade of pathophysiological responses that in turn increase blood glucose and insulin resistance. As research in this area of SH in ICU patients is sparse with conflicting results, we conducted this study to evaluate the clinical profile and prognostic outcome of Stress hyperglycemia (SH) in ICU. Aims and objectives: The main objectives of the study were to find the proportion of patients with SH in medical ICU, define the illness associated with SH, and to assess the relation of mortality with SH ratio (SHR) among stress hyperglycemics. Methods: It is a cross sectional observational study of 400 patients whose written informed consent was taken and data was collected as per structured questionnaire, covering history and laboratory investigations. Patients were followed up to assess duration of hospital stay irrespective of the outcome (discharge or death). Results: The proportion of SH in the medical ICU was 29 %. Pneumonia, acute cerebrovascular accident, congestive cardiac failure, acute coronary syndrome, family history of diabetes and female gender were found to be significant risk factors for SH. There was no significant increase in duration of hospital stay due to SH. SOFA and APACHE scores were higher among the SH group and they had higher mortality. Among patients treated for SH mortality was significantly lower. Conclusion: SH was noted in one-third of ICU admissions. It had an impact on the overall prognosis and mortality and its treatment was beneficial. Hence it is important to recognise and treat SH early in ICUs.